2020
DOI: 10.1080/10717544.2020.1831105
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and levobupivacaine co-loaded, transcriptional transactivator peptide modified nanostructured lipid carriers or lipid–polymer hybrid nanoparticles, which performed better for local anesthetic therapy?

Abstract: Sun (2020) Dexmedetomidine and levobupivacaine co-loaded, transcriptional transactivator peptide modified nanostructured lipid carriers or lipid-polymer hybrid nanoparticles, which performed better for local anesthetic therapy?,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“… 48 Yan et al developed a negatively charged, docetaxel and curcumin co-loaded nanoparticles (−38 mV) for prostate cancer therapy. 49 They argued that the negative surface charge of NPs can reduce the systematic toxicity and were important for efficient cancer therapy. Lu and colleagues also concluded that the negatively charged HA added negative charge to the NPs and obtained a more negatively charged NPs for the delivery to lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Yan et al developed a negatively charged, docetaxel and curcumin co-loaded nanoparticles (−38 mV) for prostate cancer therapy. 49 They argued that the negative surface charge of NPs can reduce the systematic toxicity and were important for efficient cancer therapy. Lu and colleagues also concluded that the negatively charged HA added negative charge to the NPs and obtained a more negatively charged NPs for the delivery to lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid materials were reported as biocompatible and less toxic, which were introduced to reduce the cytotoxicity of the drug delivery systems (Li et al., 2020 ). Zheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Li M et al. prepared transactivated transcriptional activator-modified, levobupivacaine and dexmedetomidine codelivered LPN, which showed significant improvements in skin penetration, analgesic duration, and analgesic efficacy (Li M et al., 2020 ). In another experiment, ropivacaine lipid-polymer hybrid nanoparticles (RPV-LPNs), which were formed by wrapping ropivacaine (RPV) with poly-ε-caprolactone (PCL) as the polymer core and poly(ethylene glycol)-distearoylphosphatidylethanolamine (PEG-DSPE) as the lipid shell were significantly more effective than free ropivacaine anesthesia, with a rapid response within minutes, a long duration, and high penetration (Li A et al., 2019 ).…”
Section: Local Anesthetic Compound Delivery Systemmentioning
confidence: 99%